Analisis Kemampuan Guru SD Berprestasi dalam Mengembangkan Inovasi Pembelajaran Matematika - Yuliana, Isty; Maulana, Maulana; Isrokatun, Isrokatun (Jurnal Pena Ilmiah, 2021)
Mathematics is still one of the subjects feared by elementary school students. This can affect the effectiveness of learning. Therefore, there needs to be innovation in mathematical learning. On the other hand, high school teachers are required to create or develop innovation, especially in learning. Thus, the purpose of this research is to know the efforts made by elementary school teachers who excel in developing mathematical learning innovations. The methods used in this study are qualitative descriptive. The subjects of this study were five outstanding elementary teachers from Sumedang Regency and one outstanding elementary teacher from Garut Regency. The instruments used in this study are in the form of interview guidelines, documentation studies, and questionnaires. The results showed that the innovation developed by elementary teachers excelled in developing mathematical learning innovations in the form of media and learning strategies. In addition, there are efforts to utilize technology as a support for the learning process.